Efficacy of Oral Racecadotril in Children with Acute Watery Diarrhea - Tahir, Rida; Nadeem, Muhammad Tariq; Javed, Hira; Ijaz, Maryam (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the efficacy of Racecadotril in treating acute watery diarrhea among children under 5 years of age attending Combined Military Hospital, Rawalpindi Pakistan.Study Design: Quasi-experimental study.Place and Duration of Study: Department of Pediatrics, Combined Military Hospital, Rawalpindi Pakistan, from Jul to Dec 2022.Methodology: All patients aged 6 months to 5 years with acute watery diarrhea were consecutively enrolled. All children were randomly divided into a control group (Oral Rehydration Supplement) and a study group (Racecadotril 1.5 mg/kg every eight hours). Racecadotril administration lasted until diarrhea symptoms improved or five days after the start of the treatment. From day 1 to day 5, the quantity and consistency of stool were noted. On day 5, clinical effectiveness was indicated by three stools or fewer per day.Results: Of 90 children, the overall efficacy was 61(67.8%). A significant association of efficacy was observed with the treatment group (p